Is Currency Depreciation Always Good for Improving Trade Balance? An Empirical Analysis of Selected Asian Economies - Alemu, Aye Mengistu; Lee, Jin-Sang (Indian Journal of Finance, 2014)
The aim of the present study is to investigate how depreciation could affect the export sector in selected Asian countries. The current economic environment makes it difficult to sustain trade balance among developing countries with a flexible exchange rate system among emerging economies. Theoretically, depreciation will bring positive impact on trade balance. However, it is only possible when the sum of the elasticities of demand for export and import goods is greater than unity. Accordingly, the present study first analyzed the effect of depreciation on trade balance among 14 Asian economies and found no evidence that depreciation improves trade balance. This was perhaps due to the fact that exports did not respond as expected, mainly due to the decrease in primary exports as well as manufactured products. An increase in import burden may also affect trade balance. However, the above result was challenged when we focused only on eight Asian countries that are relatively bigger, industrialized, and stable economies, and eventually we found that depreciation improved trade balance among the second group of countries.